Hubungan Pengetahuan dan Sikap Ibu Nifas terhadap Pemberian Kolostrum Pada Bayi Baru Lahir di PMB Rosa Hulu Nias Selatan Provinsi Sumatera Utara Tahun 2024 - Magdalena Duha; Rosmega Rosmega; Zulkarnain Batubara (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Colostrum is a component of breast milk in the form of a golden yellow liquid secreted by the mother from the first to the third day after giving birth. Colostrum contains 10-17 times more immune substances than mature milk, so it is very important to help form antibodies in newborn babies (Mardalena, 2017). According to WHO, the production and quality of breast milk is not affected by the nutritional condition of the mother unless the mother experiences extreme malnutrition. This could be a reason to support mothers to continue breastfeeding their newborn babies in emergency situations. (RI Ministry of Health, 2018) stated this information. WHO and UNICEF support exclusive breastfeeding through early initiation of breastfeeding within the first hour after birth, exclusive breastfeeding without giving any food or drink including water, feeding according to the newborn's desire both in the morning and evening, and avoiding the use of bottles, pacifiers , and teas (Ministry of Health, 2018). This study is an analytical research with a cross-sectional study design used to determine the RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES OF POSTPARTUM MOTHERS TOWARDS THE PROVISION OF COLOSTRUM TO NEWBORN BABIES AT PMB ROSA HULU NIAS SOUTH NORTH SUMATRA PROVINCE IN 2024. Research shows that colostrum has a significant impact on Newborns (p= 0.006). There is a significant relationship between family support and giving colostrum to newborns (p= 0.001). Mothers of Newborns are advised to seek information about giving colostrum or breast milk to Newborns through various sources such as electronic media, social media, and health workers to increase their knowledge. Provide training to health staff at the Eninta clinic to increase promotion of giving colostrum to Newborns, so that mothers and families have better knowledge about the importance of colostrum.